Focus retention, performance-based perspective from Malaysian samples - Zheng, W.B.; Kaur, S.; Yan, Z. (2009)
Performance evaluation is a necessary and beneficial process, which provides useful feedback to employees about job effectiveness and career guidance. The key employees with higher organizational performance characteristics are often entitled "talent" for their key networking status in creating the organizational intelligent capital values during the intellectual era. This paper intend to be a fair and balanced assessment standard of employee's performance characters, synthesize a conceptual scale that provides a relatively comprehensive, yet parsimonious, explanation of key degree of talents' performance characters. Especially in cross-industries sampling, it is not only in favor of catching characteristic performance features possessed by talents in creating organizational values but also revealing the internal relations between talents' performance features and their organizational behaviors based on social capital theory.